A Simulation Model of Sustained-Yield Harvest for Northern Bobwhite in South Texas - Joseph P Sands; Stephen J DeMaso; Fidel Hernández; Leonard A. Brennan; Matthew J. Schnupp; Trent W. Teinert; Dale Rollins; Robert M Perez (National Quail Symposium Proceedings, 2022)
Recommended sustainable harvest rates for northern bobwhite (Colinus virginianus) vary greatly and range from 25% to 70% of the prehunt population. Because northern bobwhite populations have declined across their geographic range, determining sustainable harvest levels is critical for effective management. Our objectives were to use simulation modeling to identify sustainable rates of bobwhite harvest, probability of population persistence, and minimum viable population estimates. We also conducted a sensitivity analysis to evaluate the impacts of harvest on northern bobwhite populations in Texas, USA. We constructed a simulation model using Program STELLA 9.0 for a hypothetical northern bobwhite population on 800 ha in the South Texas Plains USA and modeled population dynamics to 100 years over a range of harvest rates (0–40%). A 20% harvest rate produced the greatest average yields (mean ± standard error = 231 ± 10 bobwhites harvested/year). Given a quasi-extinction criterion of ≤40 bobwhites (≤0.05 bobwhite/ha), a 30% harvest rate resulted in a high probability of quasi-extinction (PE = 0.75) within 47.8 ± 2.3 years. A 40% harvest rate was not sustainable (PE = 1.0), with quasi-extinction occurring within 15.5 ± 2.6 years. Harvesting northern bobwhite populations in the South Texas Plains at rates of 20−25% of the prehunt population should maximize long-term harvest while minimizing the probability of population extinction. Spring densities of 0.60−0.80 bobwhite/ha may represent minimum viable spring densities for northern bobwhite populations in the South Texas Plains as these are the densities associated with sustainable 20-25% harvest rates. Harvest rates >30% are likely to be excessive with respect to long-term population persistence for northern bobwhite populations in the South Texas Plains.
Keywords: Colinus virginianus; northern bobwhite; population dynamics; simulation modeling; STELLA; sustained-yield harvest; Texas